Evaluation of Calcium and Protein Content in Powder and Gummy Candy from Anchovy Extract (Stolephorus commersonnii) - Hermawati, Ema; Ismyama, Dian Farida; Handayani, Marybet Tri Retno (Universitas Muhammadiyah Surakarta, 2025)
Anchovies (Stolephorus commersonnii) are a good source of calcium and protein. Intake of these nutrients is associated with child height. According to the Ministry of Health of the Republic of Indonesia's Nutrition Status Study Report, the prevalence of stunting among Indonesian children in 2022 was 21.6%, which is still higher than the World Health Organization's (WHO) standard of <20%. This study aims to optimize the formulation of anchovy extract gummy candies that meet quality standards and contain high levels of calcium and protein. Anchovy powder contains 328.64 mg/kg of calcium, 28.46% protein, 0.12% ash, and 5.3% moisture. The anchovy extract was prepared using the maceration method with a 70% ethanol solvent. Four gummy candy formulations were made based on variations in anchovy extract concentration: 10%, 7.5%, 3%, and 1.5%. Formulation 4 (F4) with 1.5% anchovy extract produced the best physical quality, with a standard deviation (SD) of <5% for the weight uniformity test. The organoleptic test results for F4 are as follows: the anchovy taste is mild, the color is dark purple, the smell is slightly aromatic, the shape is consistent with the mold, and the texture is chewy. F4 gummy candies contain 1,490.64 mg/kg of calcium, 27.49% protein, 9.17% ash, and 3.96% moisture. A serving size of one gummy (1.5 g) contains 2.24 mg of calcium, 0.41 g of protein, 0.06 g of total fat, 0.07 g of carbohydrates, 0.55 g of sugar, and 4.18 mg of sodium. F4 meets quality standards and is high in calcium and protein.